2017
DOI: 10.1590/1519-6984.08315
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of entomopathogenic nematodes in an apple orchard in Southern Brazil and its virulence to Anastrepha fraterculus (Diptera: Tephritidae) larvae, under laboratory conditions

Abstract: Entomopathogenic nematodes (EPNs) are a promising alternative to integrated control in many fruit pests. Few studies were made on the relationship of Anastrepha fraterculus natural population with native EPNs population and other biotic and abiotic factors. The aim of this work was to verify the occurrence of endemic nematodes in an apple orchard, concerning environmental conditions and technical procedure, and access isolates virulence to A. fraterculus larvae. The experiment was conducted during a year takin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
2
8
1
Order By: Relevance
“…This study found a low or uneven distribution of EPNs in the rural region evaluated in the municipality of Toribío in the department of Cauca, Colombia, which was evidenced in a low recovery frequency. Despite differences in habitats sampled and methodologies used for soil sampling and EPNs isolation, the recovery frequency obtained in this study was similar to that reported from soils of other Latin American countries such as México (6.6%, 4 positive samples out of 60) ( Delgado-Gamboa et al, 2015 ) and Chile (7%, 97 positive samples out of 1,382) ( Edgington et al, 2010 ), but different from others like Brazil (23.2%, 73 positive samples out of 315) ( Foelkel et al, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study found a low or uneven distribution of EPNs in the rural region evaluated in the municipality of Toribío in the department of Cauca, Colombia, which was evidenced in a low recovery frequency. Despite differences in habitats sampled and methodologies used for soil sampling and EPNs isolation, the recovery frequency obtained in this study was similar to that reported from soils of other Latin American countries such as México (6.6%, 4 positive samples out of 60) ( Delgado-Gamboa et al, 2015 ) and Chile (7%, 97 positive samples out of 1,382) ( Edgington et al, 2010 ), but different from others like Brazil (23.2%, 73 positive samples out of 315) ( Foelkel et al, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
“…( H. cf . safricana ), from soils of natural habitats and agricultural areas between 0 and 2,499 m.a.s.l, while in Brazil Foelkel et al (2017) recovered five EPN isolates which were closely related to Oscheius sp. from soil samples of an apple orchard (cultivar Eva) at 865 m.a.s.l., which points the variable and cosmopolitan distribution of EPNs ( Rizvi et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…In the state of Rio Grande do Sul, the occurrence of the species Steinernema feltiae, Steinernema rarum and Steinernema riobrave was reported for the first time in Brazil (BARBOSA-NEGRISOLI et al, 2010). Nematodes of the genera Oscheius are found in apple orchard (FOELKEL et al, 2017). EPNs also identified in agricultural areas of São Paulo and Paraná were H. amazonensis, Metarhabditis rainai, Oscheios tipulae and S. rarum (DE BRIDA et al, 2017).…”
Section: Isolation Of Entomopathogenic Nematodes In the West Region Omentioning
confidence: 98%
“…In addition to the potential of these entomopathogens to control insects, studies have been developed to isolate these microorganisms from the soil and to perform pathogenicity tests on insects of agricultural importance (LU et al, 2016). Soil samples and isolation of EPNs in Brazil were made in the states of Minas Gerais (ACEVEDO et al, 2005;ANDALÓ et al, 2018), Rondônia (DOLINSKI;MOINO, 2006), Rio Grande do Sul (BARBOSA-NEGRISOLI et al, 2010;FOELKEL et al, 2017), São Paulo and Paraná (DE BRIDA et al, 2017).…”
Section: Isolation Of Entomopathogenic Nematodes In the West Region Omentioning
confidence: 99%
“…The soil of many orchard environments appears to be an excellent natural habitat for EPNs as numerous EPNs could be sampled and isolated from orchard soils in various studies the past decades (e.g. see [12][13][14][15][16]). Within a favourable range of temperatures, adequate humidity and a susceptible host, effective control of underground pest stages generally requires EPNs with a mobile foraging strategy (cruisers and intermediate foraging strategies) [7].…”
Section: Epn Targeting Subterranean Pest Stages In Orchardsmentioning
confidence: 99%